Business Development Through Strategic Compensation Design in a Circular Fashion Startup: The Case of Ofelia - Reny Widiastuti; Zaenal Arifin; Majang Palupi (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
Ofelia is a brand that offers accessories made from clothing waste. This business seeks to create a new trend for women to care about environmental issues, especially clothing. Ofelia strives to provide fair and equitable compensation to its employees as part of its commitment to sustainable business. This includes fulfilling the rights of its employees, most of whom are freelancers, through output-based financial compensation and non-financial compensation. This study aims to examine the effectiveness of Ofelia's compensation implementation in improving the motivation and performance of freelance employees. The research method used was descriptive qualitative through observation, interviews, and documentation studies. Overall, Ofelia's output-based financial compensation system has not shown effective results on employee performance. However, it cannot be denied that an output-based financial compensation system makes it easier for start-up companies to control compensation based on employee performance. The non-financial compensation applied to Ofelia demonstrates positive development for each employee and supports them in completing their tasks. However, its correlation with work motivation has not been definitively proven. However, conditions that demonstrate increased employee morale provide a positive opportunity for the company to continue striving to improve employee motivation. Keywords: output-based financial compensation, non-financial compensation, performance, motivation, freelancer